Global scientific production on illicit drug addiction: a two-decade analysis - Khalili, Malahat; Mann, Karl (European addiction research, 2018)
Aims: Addiction science has made great progress in the past decades. We conducted a scientometric study in order to quantify the number of publications and the growth rate globally, regionally, and at country levels. Methods: In October 2015, we searched the Scopus database using the general keywords of addiction or drug-use disorders combined with specific terms regarding 4 groups of illicit drugs - cannabis, opioids, cocaine, and other stimulants or hallucinogens. All documents published during the 20-year period from 1995 to 2014 were included. Results: A total of 95,398 documents were retrieved. The highest number of documents were on opioids, both globally (60.1%) and in each of 5 continents. However, studies on cannabis showed a higher growth rate in the last 5-year period of the study (2010-2014). The United States, the United Kingdom, Germany, Canada, Australia, France, Spain, Italy, China, and Japan - almost all studies were from high-income countries - occupied the top 10 positions and produced 81.4% of the global science on drug addiction. Conclusion: As there are important socio-cultural differences in the epidemiology and optimal clinical care of addictive disorders, it is suggested that low- and more affected middle-income countries increase their capacity to conduct research and disseminate the knowledge in this field.